Burnout in emergency medicine professionals after 2 years of the COVID-19 pandemic: a threat to the healthcare system?. (22nd June 2022) - Petrino, Roberta; Riesgo, Luis Garcia-Castrillo; Yilmaz, Basak
Abstract : Background: Burnout is a common problem among healthcare professionals (HCPs), in particular young doctors and nurses working in emergency medical services. The coronavirus disease 2019 (COVID-19) pandemic has generated a substantial increase in the workload of those working in front-line services, and there is evidence of physical and mental distress among professionals that may have caused an increase in burnout. Objective: The objective of the study was to evaluate the level of burnout in the different professionals of emergency medical services. Design and participants: In January and February 2022, we conducted an online survey based on the Abbreviate Maslach inventory with the addition of three questions focused on possible modifying factors. The survey was disseminated to HCP via the list of European Society for Emergency Medicine contacts. Outcome measures: The analysis was based on two of the three elements of the Maslach burnout concept, 'depersonalisation', 'emotional exhaustion', and 'personal accomplishment'. Overall burnout was defined when at least one of the two elements 'depersonalisation' or 'emotional exhaustion' reached the level of high burnout. Results: The number of responders was 1925, 84% of which were physicians, 12% nurses, and 2% paramedics. Burnout was present in 62% of all responders. A high burnout level was reported for depersonalisation, emotional exhaustion, and personal accomplishment in 47%, 46%, and 48% of responders, respectively. Females reported a higher proportion of burnout compared with males 64% vs. 59%, difference −6% [95% confidence interval CI, −8 to −1.9], and nurses higher than physicians, 73% vs. 60%, difference −13 (95% CI, −18.8 to −6). Less experienced professionals reported higher levels of burnout: those with less than 5 years of experience the burnout level was 74% compared with the group with more than 10 years, 60%, difference −26% (95% CI, −32 to −19.5). Reported frequent understaffing situations were associated with a higher risk of burnout: 70% vs. 37%, difference −33% (95% CI, −41 to −25). Burnout was associated with a higher risk of desire to change the workplace: 87% vs. 40%, difference −47% (95% CI, −52 to −42). Survey responders reported having access to support programmes in 41% of cases. Conclusion: In this study, there is a high reported level of burnout among emergency HCPs. Several risk factors were identified such as being understaffed, female, or having less experience. HCPs with burnout thought more frequently about leaving the workplace, posing a threat to healthcare systems.